Filtrate Culture of Trichoderma, Gliocladium, Penicilium and Aspergillus flavus as Inhibitor on Downy Mildew on Maize - Ilmi, Nur; Sogandi, Sogandi; Hikmahwati, Hikmahwati (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Controlling downy mildew caused by Perenosclerospora philipinensis in maize plants is currently dependent on the use of synthetic pesticides; therefore, it is necessary to develop biocontrol agents as a sustainable alternative control. Filtrate cultures of biocontrol agent fungi consist of antibiotics, enzymes, and secondary metabolites that are antimicrobial in nature. We conducted the research from July to August 2024 at the Plant Disease Laboratory of the Department of Protection, Faculty of Agriculture, and the Biochemistry Laboratory of the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Hasanuddin University. This study had four parts: (1) identifying the morphology of biocontrol agent isolates and pathogenic fungi; (2) measuring growth diameter of antagonist fungi;(3) testing filtrate cultures for their ability to inhibit pathogens; and (4) testing filtrate cultures for their ability in vigor of sprouting on corn seeds. Based on morphological identification, the four biocontrol agent isolates are Trichoderma, Gliocladium, Penicillium, and Aspergillus flavus, with the best growth diameter on the Trichoderma, which is 8.5 cm on seven days. The filtrate cultures performed the best in the inhibition test on P. philipinensis, exhibiting spore damage percentages of 70-74%. The vigor test performed best on Trichoderma and Aspergillus flavus, with growth potential (GP) of 100% and 63%, respectively. Filtrate culture with biological agents has good potential for P. philipinensis spore inhibition and corn seed germination.